Field-Based Art Programming As a Facilitator for Transformative Learning Experiences in Tertiary Education: Participants Reflections on Land Arts of the American West: Participants Reflections on Land Arts of the American West - Naranjo, David Gabriel (Arte, Individuo y Sociedad, 2022)
Field-based art programming proposes a different pedagogical model to respond to contemporary challenges that artists face, ranging from ecological crises to the education and development of artists. This article analyzed interviews with field-based art programming participants across two decades, focusing on artists’ experiences through their own voices. Out of the interviews with participants from Land Arts of the American West, in which participants travel, camp, and create at different sites throughout the Southwest, the participants narrate important elements of field-based art programming. Using Mezirow’s theory of Transformative Learning, this article uses participants’ descriptions to analyze the pedagogical aspects of field-based art learning that denotes a transformative experience, distinct from what is available to them in conventional tertiary art classes. Central reoccurring themes identified include immersive nature, art-making, community, and place. Participants’ responses reveal Disorienting Dilemmas and having transformative experiences.